Noonan syndrome, PTPN11 mutations, and brain tumors. A clinical report and review of the literature. Issue 4 (22nd March 2017) - Siegfried, Aurore; Cances, Claude; Denuelle, Marie; Loukh, Najat; Tauber, Maïté; Cavé, Hélène; Delisle, Marie‐Bernadette
Abstract : Noonan syndrome (NS), an autosomal dominant disorder, is characterized by short stature, congenital heart defects, developmental delay, and facial dysmorphism. PTPN11 mutations are the most common cause of NS. PTPN11 encodes a non‐receptor protein tyrosine phosphatase, SHP2. Hematopoietic malignancies and solid tumors are associated with NS. Among solid tumors, brain tumors have been described in children and young adults but remain rather rare. We report a 16‐year‐old boy with PTPN11 ‐related NS who, at the age of 12, was incidentally found to have a left temporal lobe brain tumor and a cystic lesion in the right thalamus. He developed epilepsy 2 years later. The temporal tumor was surgically resected because of increasing crises and worsening radiological signs. Microscopy showed nodules with specific glioneuronal elements or glial nodules, leading to the diagnosis of dysembryoplastic neuroepithelial tumor (DNT). Immunohistochemistry revealed positive nuclear staining with Olig2 and pERK in small cells. SHP2 plays a key role in RAS/MAPK pathway signaling which controls several developmental cell processes and oncogenesis. An amino‐acid substitution in the N‐terminal SHP2 domain disrupts the self‐locking conformation and leads to ERK activation. Glioneuronal tumors including DNTs and pilocytic astrocytomas have been described in NS. This report provides further support for the relation of DNTs with RASopathies and for the implication of RAS/MAPK pathways in sporadic low‐grade glial tumors including DNTs. © 2017 Wiley Periodicals, Inc.